Effects of spectral nudging on precipitation extremes and diurnal cycle over CORDEX‐East Asia domain. (27th July 2018) - Tang, Jianping; Sun, Xuguang; Hui, Pinhong; Li, Yan; Zhang, Qi; Liu, Jianyong
Abstract : In this study, by using the Weather Research and Forecasting (WRF) model, the impact of spectral nudging (SN) on simulating the precipitation extremes and diurnal cycle of precipitation over Coordinated Regional Climate Downscaling Experiment‐East Asia (CORDEX‐EA) domain is evaluated. The simulations are conducted during 1989–2007 driven by the ERA‐Interim reanalysis data with different SN experiments. It is clear that WRF has the ability to reproduce the long‐term climatology as well as the extremes over Asia, while biases are generated in the experiment without SN (NOSN). The simulations with SN, especially SN6 (SN with wavenumber 6) and SN3‐UVT (SN with wavenumber 3 applied to wind and temperature), can efficiently improve the model's skill by reducing the biases of precipitation frequency and intensity as well as the extreme indices except for the consecutive dry days (CDD). The diurnal harmonics of precipitation frequency and amount are well produced by WRF, and the SN experiments also perform better than the NOSN experiment, with SN3‐UVT showing the best skill. However, the SN only with winds shows little improvement in simulating the diurnal cycles, and the additional nudging of temperature can improve the simulation only over south China and Indo‐China. It can be concluded that the strength of nudging parameters can significantly affect the simulation of precipitation, with better performance under the stronger nudging. Moreover, additional nudging of temperature can also improve the simulation. Abstract : The impact of spectral nudging on simulating the precipitation extremes and diurnal cycle of precipitation over CORDEX‐EA domain is evaluated using WRF. WRF has the ability to reproduce the long‐term climatology as well as the extremes over Asia, while biases are generated in the NOSN experiment. The SN simulations produce better the precipitation extremes and diurnal harmonics. Better simulation of precipitation is performed under the stronger nudging, and additional nudging of temperature can also improve the simulation.